Examination on the Effect of Swimming Exercises Applied with Co Enzyme Q10 and Zinc Supplementation on the Ast-Alt Metabolism in Young Athletes - Cinar, Vedat; Polat, Yahya; Akbulut, Taner; Talaghir, Laurentiu-Gabriel; Kaynak, Kerimhan; Marangoz, Irfan (Lumen Publishing House, 2018)
In that study, it has been aimed to determine the effect of zinc and CoQ10 supplementation applied with 8-week swimming exercises on AST-ALT metabolism. Our study was conducted on 36 voluntary male athletes aged 18-22 who do physical exercises actively. The participants were divided equally into 4 groups. The groups were constituted in that way: 1st Group: Group which is supplied with zinc (Z), 2nd Group: Group which is supplied with Coenzyme Q10 (Q), 3rd Group: Control Group who does physical exercises (C) and 4th Group: Group which is supplied with Zinc and Coenzyme Q10 (ZQ). At the first week of the study, AST and ALT levels of the participants were measured from the samples which were drawn from the participants at pre-exercise resting period (PRP), post-exercise pre-test fatigue (PTF) and pre-exercise post-test rested (PTR) and post-exercise post-test fatigue (PTF) after 8-week supplementation period. In consequence of the conducted analysis, it was identified that rested AST levels of the group supplied with zinc were higher than their fatigue levels after 8-week supplementation period (p<0.05). As for ALT values of the group supplied with zinc, the post-test fatigue values were found lower than the pre-exercise rested and after 8-week exercise rested values (p<0.05). The post-test fatigue (PTF) values of the control group were determined lower than their post-test rested (PTR) values (p<0.05). It was identified statistically significant differences between not only PostTF and PostTR values but also PostTR and PreTR values of the group supplied with Zinc and Coenzyme Q10 (p<0.05). Consequently, it was confirmed that zinc and CoQ10 supplementation applied with 8-week swimming exercises had influence over the AST and ALT metabolism. It can be said that the antioxidant supplementation makes significant contributions as the AST and ALT metabolism are active.
Keywords: Zinc; CoQ10; AST and ALT; swimming